2018
DOI: 10.1088/1361-6528/aaaf16
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance and photoacoustic imaging of brain tumor mediated by mesenchymal stem cell labeled with multifunctional nanoparticle introduced via carotid artery injection

Abstract: Our results demonstrated the feasibility of tracking carotid artery-injected SPIO@Au-labeled MSCs in vivo via MR and PA imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 50 publications
1
56
0
Order By: Relevance
“…Numerous studies have described flow cytometric evaluation of MSC surface markers in order to assess the differentiation potential of MSCs following nanoparticle internalization. 35,[45][46][47][48][49] In agreement with our findings, their results consistently reported no effects on surface-marker expression or osteogenic and adipogenic differentiation ability. These results showed that nanoparticlelabeling did not alter MSC differentiation or characteristics higher than 50 µg/mL did not enhance cell-uptake efficiency, at 100 µg/mL, the nanoparticles tended to aggregate in the culture medium and adhere to the plate.…”
Section: Characterization Of Mscs Loaded With Iron Oxide Nanoparticlessupporting
confidence: 90%
“…Numerous studies have described flow cytometric evaluation of MSC surface markers in order to assess the differentiation potential of MSCs following nanoparticle internalization. 35,[45][46][47][48][49] In agreement with our findings, their results consistently reported no effects on surface-marker expression or osteogenic and adipogenic differentiation ability. These results showed that nanoparticlelabeling did not alter MSC differentiation or characteristics higher than 50 µg/mL did not enhance cell-uptake efficiency, at 100 µg/mL, the nanoparticles tended to aggregate in the culture medium and adhere to the plate.…”
Section: Characterization Of Mscs Loaded With Iron Oxide Nanoparticlessupporting
confidence: 90%
“…The main and most used are bioluminescent optical imaging (BLI), magnetic resonance imaging (MRI), and nuclear imaging techniques. [50][51][52][53][54][55] For a in-depth review on MSC homing imaging, see Reference 43. In a syngeneic rat model, luciferase charged MSCs, injected in the right common carotid artery, were tracked by in vivo BLI into right frontal lobe, co-localizing with glioma cells. Similar results were observed using a fluorescent vital dye, after injection into the same site.…”
Section: Overview Of Msc Functional Propertiesmentioning
confidence: 99%
“…53 Other technical studies validate the use of gold-coated nanoparticles or ferritin heavy chain expressing MSCs as marker to track by MRI. 50,54 Migration of AT-MSCs to target brain tumor-initiating cells was studied by in vivo BLI analysis using fluorescent magnetic nanoparticles. 52,56 57,58 promoting macrophages transformation from M1 to M2 anti-inflammatory phenotype, 59 or contributing to immune homeostasis.…”
Section: Overview Of Msc Functional Propertiesmentioning
confidence: 99%
“…Thus far, in oncology, the role of these MRI-guided theranostics is mainly restricted to tracking transplanted cells in animal models ( Table 2). [67][68][69][70][71][72] Intravenous (I.V.) injection is a frequently used medication delivery route and is commonly applied for MSC delivery in both animal models and clinical trials, although extensive MSC recruitment into the tumor site of gliomas upon regional injection into the cerebral hemisphere or intra-arterial injection via the internal carotid artery has been observed in many studies, 71,[73][74][75] the homing ability of systemically injected MSCs toward brain tumors has been less evidenced by cellular imaging, because most MSCs are entrapped in the reticuloendothelial system and pulmonary vasculature after I.V.…”
Section: Mri-tracking Of Msc Tumor-homingmentioning
confidence: 99%